The role of mythical symbols in the formation of the cognitive layer of a literary text - Sultan Е.Б.; Aituganova С.Ш. (Bulletin of L.N. Gumilyov Eurasian National University. PHILOLOGY Series, 2024)
The article examines the mythical symbols that find application in the literary text and their role in the formation of the cognitive layer of the literary text. It is known that the literary text consists of form and content parts. The content of a literary text forms the basis of a number of cognitive layers. During the process of reading a literary text, the reader is not only immersed in information, but also connected to some cognitive process. Therefore, the understanding of a literary text as a semiotic system allows us to access the cognitive information behind the text. Semiotic symbols, including symbolic representations, play a special role in the formation of such a cognitive layer. Consequently, the focus of our research will focus on the phenomena of mythological symbolism, which are intertwined with the mythical consciousness found in the composition of the literary text and continue with the author’s knowledge. Examples from real fiction texts were identified for the purpose of the study. The purpose of the study is to differentiate the role of mythical symbols in the formation of the cognitive layer of a literary text. The level of folk mythical thinking and mythical consciousness, which has developed over the centuries, is included in the system of artistic thinking, speech of writers of the nation, and is reflected in literary texts. Thus, by focusing on the influence of mythical symbols on the structure of the semiotic system in the background, cognitive layer of a literary text allows us to fully understand the text, analyze how it affects the reader’s perception. In the course of the study, methods of semiotic, symbolic, conceptual, and semantic analysis are used with methods of theoretical accumulation, differentiation, and comparison. The method of semiotic analysis is particularly effective in deciphering the mythological codes contained in a literary text. The study reveals the importance of mythical symbols in the formation of the cognitive layer of a literary text and the influence of mythical symbolism on the content part of a literary text.